The Influence of Orthographic Units Across Korean Children of Different Ages in Hangul Reading - Ju, Yeongsil; Sambai, Ami; Uno, Akira (Frontiers in Psychology, 2022)
Using the dual-route reading model as a framework, this study investigated two research questions on Hangul reading: (1) Is the lexical reading process involved in the reading performance of Korean-speaking children? (2) Does the strengths of the influence of orthographic units (e.g., letters, syllable blocks, words) vary across children of different ages? To answer these questions, we tested the effects of age, frequency, lexicality, and two types of length—that is, the numbers of letters (letter-length) and syllable blocks (syllable block-length)—and the interactions of these factors in the reading performance of Korean-speaking preschool and primary school children from first to third grade. Regarding reading latencies, there was a significant three-way interaction of age × lexicality × length regardless of the type of length. This interaction indicated that, for words only, the interaction between age and length was significant; the length effect was smaller as children’s age increased. When reading latencies for words were analyzed with a mixed-effect model consisting of three factors—age, frequency, and length—neither a main effect of syllable block-length nor an interaction of syllable block-length with age was significant. In contrast, the interaction of age × letter-length in word reading latencies remained significant; the length effect was smaller as children’s age increased. In addition, the frequency effect was significant and interacted significantly with age; the frequency effect was larger as children’s age increased. In conclusion, Korean-speaking children use the lexical process in addition to the non-lexical process when reading Hangul words because of a significant frequency effect. Importantly, as children grow up, a larger orthographic unit, that is, words, is more strongly related to reading performance, whereas the influence of a smaller orthographic unit, that is, letters, decreases.